2016
DOI: 10.1177/0271678x16670411
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and stroke: Can we translate from rodents to patients?

Abstract: Obesity is a risk factor for stroke and is consequently one of the most common co-morbidities found in patients. There is therefore an identified need to model co-morbidities preclinically to allow better translation from bench to bedside. In preclinical studies, both diet-induced and genetically obese rodents have worse stroke outcome, characterised by increased ischaemic damage and an altered inflammatory response. However, clinical studies have reported an ‘obesity paradox’ in stroke, characterised by reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 161 publications
(289 reference statements)
4
46
1
2
Order By: Relevance
“…Similar findings have been shown in genetically obese T2D animals (reviewed in [11]). The ones employing more physiological and clinically relevant obese/T2D models (induced by high-fat diet (HFD)) have mostly focused on the acute outcome (infarct size and neurological impairment) after stroke and, in the cases with more long-term outcome measures, the increase in the stroke injury was likely a determinant factor for decreased neurological recovery (reviewed in [11]). At present, it is therefore undetermined whether T2D induced by a chronic obesogenic diet affects long-term stroke recovery and if so, whether this effect is related to the impairment of brain's self-repair mechanisms.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar findings have been shown in genetically obese T2D animals (reviewed in [11]). The ones employing more physiological and clinically relevant obese/T2D models (induced by high-fat diet (HFD)) have mostly focused on the acute outcome (infarct size and neurological impairment) after stroke and, in the cases with more long-term outcome measures, the increase in the stroke injury was likely a determinant factor for decreased neurological recovery (reviewed in [11]). At present, it is therefore undetermined whether T2D induced by a chronic obesogenic diet affects long-term stroke recovery and if so, whether this effect is related to the impairment of brain's self-repair mechanisms.…”
Section: Introductionsupporting
confidence: 85%
“…Experimental stroke studies using toxin-induced hyperglycemia have shown that, similar to clinical observations, the neurological recovery in hyperglycemic animals is significantly attenuated [9,10]. Similar findings have been shown in genetically obese T2D animals (reviewed in [11]). The ones employing more physiological and clinically relevant obese/T2D models (induced by high-fat diet (HFD)) have mostly focused on the acute outcome (infarct size and neurological impairment) after stroke and, in the cases with more long-term outcome measures, the increase in the stroke injury was likely a determinant factor for decreased neurological recovery (reviewed in [11]).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Along with metabolic derangements, obesity is associated with significant and protracted increase in inflammatory markers, and as such it has been described as a low-grade chronic inflammatory state. 42 Low-grade inflammation and systemic oxidative stress have proven to be damaging for the endothelium, shifting it toward a prothrombotic state. Platelet reactivity, enhanced coagulation, and impaired fibrinolysis are other recognized mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies suggest that apart from molecular factors secreted in the setting of obesity and ischemic stroke, the integrity of the blood–brain barrier is affected in obese subjects. Thus, it was reported that at 4 and 24 h after the ischemic event, the obese mice have a significant blood–barrier breakdown characterized by an increased amount of endothelial vesicles, suggesting vascular damage (Haley & Lawrence, ). However, it is not clear which are the factors that modulate the blood–brain barrier damage.…”
Section: Introductionmentioning
confidence: 99%